2019
DOI: 10.1128/jvi.00840-19
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Stalk Enhances Immunogenicity of the Influenza Virus Neuraminidase

Abstract: Influenza viruses express two surface glycoproteins, the hemagglutinin (HA) and the neuraminidase (NA). Anti-NA antibodies protect from lethal influenza virus challenge in the mouse model and correlate inversely with virus shedding and symptoms in humans. Consequently, the NA is a promising target for influenza virus vaccine design. Current seasonal vaccines, however, poorly induce anti-NA antibodies, partly because of the immunodominance of the HA over the NA when the two glycoproteins are closely associated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…An important challenge in inducing NA directed immune responses involves overcoming the immunodominance of HA over NA. In an attempt to subvert the HA immunodominance, a recent study generated two recombinant influenza viruses based on the H1N1 stain A/Puerto Rico/8/1934 (PR8) in which the NA stalk domain was extended by 15-30 amino acids (Broecker et al, 2019b). Using formalin-inactivated viruses expressing wildtype NA or the extended NA, the authors demonstrated that the extended NA stalk induced higher anti-NA IgG responses than the unmodified NA in mice (Broecker et al, 2019b).…”
Section: Neuraminidase-directedmentioning
confidence: 99%
See 2 more Smart Citations
“…An important challenge in inducing NA directed immune responses involves overcoming the immunodominance of HA over NA. In an attempt to subvert the HA immunodominance, a recent study generated two recombinant influenza viruses based on the H1N1 stain A/Puerto Rico/8/1934 (PR8) in which the NA stalk domain was extended by 15-30 amino acids (Broecker et al, 2019b). Using formalin-inactivated viruses expressing wildtype NA or the extended NA, the authors demonstrated that the extended NA stalk induced higher anti-NA IgG responses than the unmodified NA in mice (Broecker et al, 2019b).…”
Section: Neuraminidase-directedmentioning
confidence: 99%
“…In an attempt to subvert the HA immunodominance, a recent study generated two recombinant influenza viruses based on the H1N1 stain A/Puerto Rico/8/1934 (PR8) in which the NA stalk domain was extended by 15-30 amino acids (Broecker et al, 2019b). Using formalin-inactivated viruses expressing wildtype NA or the extended NA, the authors demonstrated that the extended NA stalk induced higher anti-NA IgG responses than the unmodified NA in mice (Broecker et al, 2019b). Similarly, extension of the NA stalk from H3N2 virus increased NA-specific antibody responses (Broecker et al, 2019b).…”
Section: Neuraminidase-directedmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many groups are working to increase the immunogenicity of NA through development of new vaccine formulations and strategies. [31][32][33] Similarly, antibodies that target the conserved ectodomain of the influenza matrix 2 protein (M2e) were protective in preclinical and clinical settings. 34 Because of its abundance on the surface of the virus, HA has been the most attractive vaccine target.…”
Section: Examples Of Recent Technologies To Study Host-virus and Host-vaccine Responses Of Importance For Future Influenza Vaccine Develomentioning
confidence: 99%
“…The antigenicity of NA has long been detailed using monoclonal antibodies (mAbs) isolated from immunized and/or infected mice, which provided an initial understanding of its distinct antigenic regions-some of which span adjacent protomers-as well as mechanisms of both enzymatic inhibition and protection [21][22][23][24][25] . Although an NA-based vaccine, extracted from viral membranes and inactivated by formalin, improved humoral NA-directed inhibition compared to commercial vaccines in humans in a Phase I clinical trial more than 25 years ago 26,27 , only preclinical studies of NA-based vaccines have been reported since [28][29][30][31][32] . More recently, studies comparing antibodies elicited by infection or immunization with split virus vaccines in humans as well as mice have clearly demonstrated that infection results in substantially more robust NA-directed humoral responses 33 .…”
Section: Introductionmentioning
confidence: 99%